2007
DOI: 10.1109/tcad.2006.888284
|View full text |Cite
|
Sign up to set email alerts
|

An Application-Specific Design Methodology for On-Chip Crossbar Generation

Abstract: Abstract-Designing a power-efficient interconnection architecture for MultiProcessor Systems-on-Chips (MPSoCs) satisfying the application performance constraints is a nontrivial task. In order to meet the tight time-to-market constraints and to effectively handle the design complexity, it is essential to provide a computer-aided design tool support for automating this task. In this paper, we address the issue of "application-specific design of optimal crossbar architecture" satisfying the performance requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…In recent years, some efficient interconnect architectures dedicated for a hardware fabric have been proposed to exploit the advantages of the fabric such as DESA NoC [Roca et al, 2012] or low-cost and specific-application crossbar in [Hur et al, 2012;Murali et al, 2007] developed for FPGAs. Additionally, many hybrid interconnects both in mixed NoC topologies and in mixed architectures have been proposed to improve the hybrid interconnect throughput or reduce hardware cost as presented in Section 2.2.…”
Section: Hardware Level Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, some efficient interconnect architectures dedicated for a hardware fabric have been proposed to exploit the advantages of the fabric such as DESA NoC [Roca et al, 2012] or low-cost and specific-application crossbar in [Hur et al, 2012;Murali et al, 2007] developed for FPGAs. Additionally, many hybrid interconnects both in mixed NoC topologies and in mixed architectures have been proposed to improve the hybrid interconnect throughput or reduce hardware cost as presented in Section 2.2.…”
Section: Hardware Level Optimizationmentioning
confidence: 99%
“…An n×n crossbar can quickly become prohibitively expensive as its cost increases by n 2 . To reduce the cost, many studies focusing on application-specific crossbars have been reported such as in [Hur et al, 2007], [Murali et al, 2007].…”
mentioning
confidence: 99%
“…Researches on bus matrix have tried to find out optimal bus matrix architectures considering the number of buses and arbitration schemes [3] [4]. However, these works focusing on on-chip communication architectures have paid no attention to low-level details of memory subsystem as considered in this paper.…”
Section: Related Workmentioning
confidence: 99%
“…Previous works on the design space exploration of communication architecture have mainly focused on the high performance embedded systems of increasing complexity [1][2][3] [4]. Since the performance is of primary concern, architecture exploration has been performed with the abstracted models of communication and memory system, based on approximate cost models.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the IP integration problem, earlier work mainly focused on static bridge designs [44,75]. Since the static approaches are inherently non-scalable and limited in the ability to provide high performance in cases where the traffic characteristics vary dynamically, a number of automatic designs were proposed to dynamically optimize the bus-based architectural topology [98,52,151]. Moreover, several design methodologies and design flow for customizing these architectures to adapt to traffic characteristics have further been studied [79,48,191].…”
Section: Related Workmentioning
confidence: 99%